ALDH1 expression and potential clinical implications in chronic inflammatory periapical lesions - Zilda Betânia Barbosa Medeiros de Farias; Leorik Pereira da Silva; José Alcides Almeida de Arruda; Jade de Souza Cavalcante; Híttalo Carlos Rodrigues de Almeida; Maria Cristina Valença de Oliveira; Lélia Batista de Souza; Ana Paula Veras Sobral (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract: Aldehyde dehydrogenase 1 (ALDH-1) is a marker of stem cells in a variety of diseases, but its role in individuals with chronic inflammatory periapical lesions remains unknown. The aim of this study was to investigate the presence of cells with a stem cell profile based on the immunoexpression of ALDH-1 in periapical granulomas (PGs) and radicular cysts (RCs). A total of 51 cases of periapical lesions (25 PGs and 26 RCs) were subjected to immunohistochemical study. The anti-ALDH-1 antibody was applied using the immunoperoxidase technique. An immunoexpression score (intensity vs. percentage of cells) was used, with the cases being classified as low expression (score: 0 to 4) and high expression (score: 6 to 9). The Chi-square test was used with a 5% level of significance. Immunoexpression of ALDH-1 was detected in all cases of PGs and RCs. In PG cases, the expression was diffuse in connective tissue cells, with most cases exhibiting high expression (n = 18; 69.2%), while in RC cases the expression revealed focal distribution in cells of the capsule and epithelial cells of the cystic lining, with most cases classified as low expression (n = 18; 72%). Significant differences in the expression scores of ALDH-1 were observed in PGs (p = 0.003). The variable expression of ALDH-1 suggests the presence of cells with stem cell profiles in PGs and RCs. These findings suggest that periapical tissues infiltrated by chronic inflammation can recruit important cells for the repair or evolution of periapical lesions.